Răspuns :
a)3/4*1 3/5+1 3/5*1 3/8-1 1/2*1 3/5 =
1 3/5 x (3/4 + 1 3/8 - 1 1/2) =
8/5 x ( 3/4 + 11/8 - 3/2) =
8/5 x ( (6 + 11- 12)/8) =
8/5 x 5/8 =
1
1 3/5 x (3/4 + 1 3/8 - 1 1/2) =
8/5 x ( 3/4 + 11/8 - 3/2) =
8/5 x ( (6 + 11- 12)/8) =
8/5 x 5/8 =
1
3/4*1 3/5+1 3/5*1 3/8-1 1/2*1 3/5 =
= 3/4 × 8/5 +5/8 ×11/8 -3/2 ×8/5 =
= 3 × 2/5 + 1/5 ×11-3 ×4/5 =
= 6/5 + 11/5 - 12/5 =
= (6+11-12)/5 = 5/5 =1
= 3/4 × 8/5 +5/8 ×11/8 -3/2 ×8/5 =
= 3 × 2/5 + 1/5 ×11-3 ×4/5 =
= 6/5 + 11/5 - 12/5 =
= (6+11-12)/5 = 5/5 =1